A Chorus of the Winds—On Saturn!. Issue 5 (30th May 2018) - Read, P. L.
Abstract: Results from the recently completed Cassini mission (Guerlet et al., 2018, https://doi.org/10.1002/2017JE005419 ) have demonstrated that Saturn's tropical stratosphere hosts an intriguing oscillation in its zonal (east‐west) flow that is a direct analog of the Earth's stratospheric quasi‐biennial oscillation or semiannual oscillation. The new results represent a significant advance in characterizing this phenomenon on Saturn, though a number of difficult questions are still outstanding. Is Saturn's equatorial oscillation phase‐locked to its seasonal cycle? How many other planets in our Solar System might host such analogs of the quasi‐biennial oscillation? Plain Language Summary: It is nearly 60 years since it was discovered that the winds in the Earth's tropical upper atmosphere undergo an almost regular reversal from eastward to westward flow and back with a repeat cycle of around 2 years. The accepted explanation is due to waves in the stratosphere that are generated by convection in the lower atmosphere. Although confined to the tropics, its indirect influence is felt much further afield across the Earth, affecting the predictability of the climate at temperate latitudes. But is this kind of phenomenon found on other planets? In newly published research by Sandrine Guerlet and colleagues, measurements from the Cassini orbiter have been used to show that Saturn also exhibits a similar stratospheric wind reversal but with a period of around 15 Earth years (half of Saturn's year). The new results make a convincing case that Saturn's winds change direction periodically for much the same physical reasons as on Earth. Together with recent observations of wind reversals seen on Jupiter (with a period of around 4 Earth years) and hints of similar phenomena in Venus's atmosphere, this may suggest that such cyclic wind reversals are a common feature of almost all planetary atmospheres. Key Points: The year 2018 represents an important anniversary for the Earth's QBO Recent results from Cassini convincingly confirm that a similar phenomenon occurs on Saturn Similar wave‐driven zonal flow phenomena likely occur in the atmospheres of other planets